Social Security Obstacles for Workers in Indonesia: Indonesian Family Life Survey 2014 Study - Indah Sari , Rahmaini (Talenta Publisher, 2023)
This article aims to look at the social security constraints for workers in Indonesia with the variable determinants of employment status, type of social security, and budget for social security. The study uses quantitative research methods with descriptive statistics. Based on 2014 IFLS data, the research results show that informal workers still have a weak social security budget plan with an average of IDR. 317,200 every month. Informal workers only have 4% of social security, namely 87 people. The majority of informal workers have not been touched by the social security employment program due to community access to the social security institution itself.